Application of Magnetic Aquatic Plant Biochar for Efficient Removal of Antimony from Water: Adsorption Properties and Mechanism - Luyi Nan; Yuting Zhang; Min Liu; Liangyuan Zhao; Yuxuan Zhu; Xun Zhang (Separations)
Antimony (Sb) pollution in natural water bodies can cause significant harm to aquatic ecosystems. Currently, the utilization of chemicals in water bodies presents disadvantages, such as the hardship in collecting dispersed flocs and the incomplete elimination of pollutants. In the present research, a novel type of efficient adsorbent material for the magnetic recovery of Sb was proposed: the magnetic aquatic plant biochar. Its adsorption characteristics and mechanism were deeply investigated. The results demonstrated that, among the three types of aquatic plants, the magnetic biochar of Arundo donax magnetic biochar (LMBC) displayed the most superior adsorption effect on Sb. Under optimal adsorption conditions (pyrolysis temperature of 300 °C, dosage of 100 mg, pH of 8), the removal rate of Sb by LMBC exceeded 97%. The adsorption rate of Sb by LMBC was relatively rapid, and the kinetics of adsorption conformed to a pseudo-second-order kinetic model. The adsorption isotherm was consistent with the Langmuir and Freundlich models, and the maximum adsorption capacity of Sb reached 26.07 mg/g, suggesting that the adsorption process pertained to the adsorption of multi-molecular layers. The influence of coexisting ions on the adsorption effect of LMBC was insignificant. The SEM characterization results revealed that LMBC mainly consisted of the elements C and O. The BET characterization results demonstrated that the magnetization modification augmented the specific surface area by approximately 30 times to reach 89.14 m2/g, and the pore volume increased by twofold to 0.18 cm3/g, creating a favorable condition for Sb adsorption. The FTIR, XRD, and XPS results indicated that the surface of LMBC was rich in carboxyl and hydroxyl groups and was successfully loaded with Fe2O3 and Fe3O4. LMBC not only facilitates the resourceful utilization of aquatic plant waste but also effectively removes antimony (Sb) pollution through its magnetic properties. This dual functionality presents promising application prospects for the efficient adsorption and removal of Sb from water.